Omega-3 Fatty Acids Protect Fatty and Lean Mouse Livers After Major Hepatectomy. Issue 2 (August 2017) - Linecker, Michael; Limani, Perparim; Kambakamba, Patryk; Kron, Philipp; Tschuor, Christoph; Calo, Nicolas; Foti, Michelangelo; Dufour, Jean-François; Graf, Rolf; Humar, Bostjan; Clavien, Pierre-Alain
Abstract : Objective: The aim of this study was to assess the effect of Ω3 fatty acids (Ω3FA) on fatty and lean liver in hepatic surgery. Background: The global spread of energy-dense diets has led to an endemic rise in fatty liver disease and obesity. Besides metabolic pathologies, steatosis enhances hepatic sensitivity to ischemia reperfusion (I/R) and impedes liver regeneration (LR). Steatosis limits the application of liver surgery, still the main curative option for liver cancer. Ω3FA are known to reverse steatosis, but how these lipids affect key factors defining surgical outcomes—that is, I/R, LR, and liver malignancy—is less clear. Methods: We established a standardized mouse model of high fat diet (HFD)-induced steatosis followed by Ω3FA treatment and the subsequent assessment of Ω3FA effects on I/R, LR, and liver malignancy (n = 5/group), the latter through a syngeneic metastasis approach. Fatty liver outcomes were compared with lean liver to assess steatosis-independent effects. Nonparametric statistics were applied. Results: Ω3FA reversed HFD-induced steatosis and markedly protected against I/R, improved LR, and prolonged survival of tumor-laden mice. Remarkably, these beneficial effects were also observed in lean liver, albeit at a smaller scale. Notably, mice with metastases in fatty versus lean livers were associated with improved survival. Conclusions: Ω3FA revealed multiple beneficial effects in fatty and lean livers in mice. The improvements in I/R injury, regenerative capacity, and oncological outcomes await confirmatory studies in humans. Abstract : Supplemental Digital Content is available in the text